1993
DOI: 10.1128/mcb.13.9.5898
|View full text |Cite
|
Sign up to set email alerts
|

Elements controlling follicular expression of the s36 chorion gene during Drosophila oogenesis.

Abstract: An 84-bp proximal regulatory region (PRR) of the DrosophUa melanogaster s36 chorion gene is sufficient for directing proper temporal and spatial expression of a reporter gene in three domains of the follicle: anterior, posterior, and main body. Here we show that the fidelity of PRR-directed s36 expression is dependent on the proper dorsal-ventral differentiation of the foilicular epithelium, which requires the Drosophila epidermal growth factor receptor homolog. Transgenic analysis of site-directed mutants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Surprisingly, while Slbo2.6GAL4 UAS-EcR-DN does repress effectively Cp15 expression in the main body FC, it does not repress Cp15 expression in the centripetal FC where Slbo2.6 expression is high (with similar results for Cp16,18,19,36,and 38). The tissue-specific requirement for EcR regulation of Cp gene expression is consistent with previous work showing that Cp gene expression in the FC relies on composite tissue-specific promoter elements (Tolias et al, 1993). Amplification of the chorion protein genes is controlled by origin recognition complexes (ORCs), which act through conserved cis-acting amplification control elements (ACE elements, reviewed in Claycomb and Orr-Weaver, 2005).…”
Section: Ecr Is Required For Fc Migration and Differentiationsupporting
confidence: 70%
“…Surprisingly, while Slbo2.6GAL4 UAS-EcR-DN does repress effectively Cp15 expression in the main body FC, it does not repress Cp15 expression in the centripetal FC where Slbo2.6 expression is high (with similar results for Cp16,18,19,36,and 38). The tissue-specific requirement for EcR regulation of Cp gene expression is consistent with previous work showing that Cp gene expression in the FC relies on composite tissue-specific promoter elements (Tolias et al, 1993). Amplification of the chorion protein genes is controlled by origin recognition complexes (ORCs), which act through conserved cis-acting amplification control elements (ACE elements, reviewed in Claycomb and Orr-Weaver, 2005).…”
Section: Ecr Is Required For Fc Migration and Differentiationsupporting
confidence: 70%
“…Although our methods may miss subtle defects in main-body chorion, shark may play a DA-cell-specific role in the production/formation of chorion. Although regulatory sequences and a putative binding protein drive specific spatial expression of chorion-reporter constructs (Tolias and Kafatos, 1990;Tolias et al, 1993), no reported mutants disrupt DA-specific chorion expression.…”
Section: Discussionmentioning
confidence: 99%
“…Short (less than 100-400 bp) segments of 5 0 -flanking DNA are sufficient to confer correct tissue-specific expression and precise temporal regulation of the transgenes Romano et al, 1988). Cis-acting regulatory elements, identified by mutational analysis, include an essential positive element, characterized by the sequence TCACGT that is conserved in all the chorion gene promoters, negative and positive elements that confer temporal (early or late) specificity, and elements defining spatially restricted expression (review: Orr-Weaver, 1991;Tolias et al, 1993;Mariani et al, 1996). In the latter case, the elements delineate expression in specific subregions of the epithelial surface, notably at the anterior and posterior poles and at the dorsal-anterior surface, where the dorsal appendages are formed (Parks and Spradling, 1987;Tolias and Kafatos, 1990).…”
Section: Chorion Genes and Regulation Of Chorion Gene Expression P0935mentioning
confidence: 99%